Ex Vivo Expanded Allogeneic Mesenchymal Stem Cells with Bone Marrow Transplantation Improved Osteogenesis in Infants with Severe Hypophosphatasia. Issue 10 (October 2015) - Taketani, Takeshi; Oyama, Chigusa; Mihara, Aya; Tanabe, Yuka; Abe, Mariko; Hirade, Tomohiro; Yamamoto, Satoshi; Bo, Ryosuke; Kanai, Rie; Tadenuma, Taku; Michibata, Yuko; Yamamoto, Soichiro; et al.
Patients with severe hypophosphatasia (HPP) develop osteogenic impairment with extremely low alkaline phosphatase (ALP) activity, resulting in a fatal course during infancy. Mesenchymal stem cells (MSCs) differentiate into various mesenchymal lineages, including bone and cartilage. The efficacy of allogeneic hematopoietic stem cell transplantation for congenital skeletal and storage disorders is limited, and therefore we focused on MSCs for the treatment of HPP. To determine the effect of MSCs on osteogenesis, we performed multiple infusions of ex vivo expanded allogeneic MSCs for two patients with severe HPP who had undergone bone marrow transplantation (BMT) from asymptomatic relatives harboring the heterozygous mutation. There were improvements in not only bone mineralization but also muscle mass, respiratory function, and mental development, resulting in the patients being alive at the age of 3. After the infusion of MSCs, chimerism analysis of the mesenchymal cell fraction isolated from bone marrow in the patients demonstrated that donor-derived DNA sequences existed. Adverse events of BMT were tolerated, whereas those of MSC infusion did not occur. However, restoration of ALP activity was limited, and normal bony architecture could not be achieved. Our data suggest that multiple MSC infusions, following BMT, were effective and brought about clinical benefits for patients with lethal HPP. Allogeneic MSC-based therapy would be useful for patients with other congenital bone diseases and tissue disorders if the curative strategy to restore clinically normal features, including bony architecture, can be established.